Pengaruh Struktur Modal, Likuiditas, dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Anggita Qurota A’yun; Ayu Noviani Hanum; Nurcahyono Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the influence of independent commissioners, capital receipts, liquidity, and company size on company value with profitability as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. This study used purposive sampling techniques. Thesamples used in this study were 17 food and beverage companies listed on the Indonesia Stock Exchange during the 2017-2021 period, so based on predetermined criteria, the number of samples was 85 samples. The analysis used in this study is logistic regression analysis using SPSS version 25 as a calculation tool. Based on the results given in this study, it shows that capital structure and profitability have an effect on firm value, while liquidity and firm size have no effect on firm value. The predictive ability of the four variables on firm value is 50.2%, while the other 49.8% comes from other.Keywords: capital receipts, liquidity, and company size on company value with profitability as an intervening variable